EVALUATION OF DISC BRAKE ON A HONDA VARIO 150 ESP K59 MOTORCYCLE - Adhita Prasetia; Fitra Rizkiarjo (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The effectiveness of the braking system on a motorcycle is one of the important things that will affect the rider. The brake effectiveness factor and the magnitude of the braking force are important things that must be considered in the construction of the brake system used in motorized vehicles which will affect the stability and safety of the rider. The purpose of this study was to evaluate the brake effectiveness factor and braking force of motorcycle disc brakes, which are usually used on the front wheels of two wheeled motorbikes. The brake construction to be evaluated is the disc brake construction on the Honda Vario 150 eSP K59 motorcycle. Furthermore, the calculation and design drawing of disc brakes using Catia software are carried out. Then to evaluate we perform an analysis of the braking force using disc discs with different diameters. The evaluation results obtained a Brake Effectiveness Factor (FER) of 0.64 and the result of the braking force with a disc of 551.35 N, the most effective use of a disc with a diameter of 220 mm is felt to be better in providing stability and safety for Honda Vario 150 eSP K59 motorcycle riders.